2005
DOI: 10.1017/s104795110500082x
|View full text |Cite
|
Sign up to set email alerts
|

Employment and advice regarding careers for adults with congenital heart disease

Abstract: (2005) Employment and advice regarding careers for adults with congenital heart disease. Cardiology in the Young, 15 (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 15 publications
4
45
1
Order By: Relevance
“…5,14 As survival rate has improved, good functional outcome including exercise capacity, education and occupation in the longterm become important in patients with CHD. 12,[19][20][21][22] However, in general, many patients with adult CHD may have an inadequate functional outcome. [19][20][21][22] Crossland et al showed that 33% of adult CHD patients were unemployed whatever the severity of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…5,14 As survival rate has improved, good functional outcome including exercise capacity, education and occupation in the longterm become important in patients with CHD. 12,[19][20][21][22] However, in general, many patients with adult CHD may have an inadequate functional outcome. [19][20][21][22] Crossland et al showed that 33% of adult CHD patients were unemployed whatever the severity of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The receipt of structured career/employment advice has been shown to be associated with a higher rate of employment (73%) than no career/ employment counseling (46%). 158 Discrimination is prohibited in all aspects of the work process, including hiring, advancement, compensation, and job training. It is unlawful for the employer to question an applicant about a disability or require a medical examination unless the information is necessary for specific job-related performance.…”
Section: Career Counselingmentioning
confidence: 99%
“…35 As many adults with CHD prepare to enter the job market and establish a career, 36 careful consideration of both physical and psychological capabilities should be discussed with their cardiologist so that realistic employment options are explored. Crossland et al 37 demonstrated that structured career and employment advice has been shown to be associated with a higher rate of employment (73%) than no such counseling (46%). Therefore, a review of the AHA published guidelines "Recreational and Occupational Recommendations for Young Patients With Heart Disease" 38 with patients with CHD and their parents should be performed to objectively assist with occupational counseling.…”
Section: Knowledge Of the Legislative Aspects Of Employment And Advocacymentioning
confidence: 99%